IPTEKS PENINGKATAN LABA PADA PT. BANK RAKYAT INDONESIA (PERSERO) TBK - Purba, Yelfindi; Ilat, Ventje (Universitas Sam Ratulangi, 2018)
Technological advances affect all aspects of life today, not least in the financial sector, namely banking. Banks are one of the institutions that affect the economy, banks also help people in managing their finances. For this reason, the writing of this article aims to see the bank’s business as a customer centered trust business, in utilizing technological advancement to improve the efficiency of operational activities and service quality, and competitiveness which also includes increasing the number of customer so as to reduce operating costs which will ultimately increase profits bank.Keywords: technology advancement, banking profit